Ekstrak Andaliman (Zanthoxylum Acanthopodium) dan Bawang Putih (Allium Sativum L.) terhadap Pertumbuhan Bakteri Staphylococcus Aureus dan Eschericia Coli - Arbi, Faisal; Nasution, Sri Wahyuni; Nasution, Ali Napiah (Journal of Telenursing (JOTING), 2024)
The purpose of this study was to see the comparison of the effectiveness of andaliman and garlic against staphylococcus aureus and eschericia coli bacteria. The research method used Post Test Only Control Group. The results of the antibacterial effectiveness test of ethanol extract of andaliman plants on the growth of Staphylococcus aureus bacteria at a concentration of 15% obtained the highest average clear zone diameter from the treatment group, namely 6.36 mm, having a moderate response to the growth of Staphylococcus aureus bacteria. While the antibacterial effectiveness of ethanol extract of andaliman plants on the growth of eschericia coli bacteria at concentrations of 5%, 10% and 15% obtained the average clear zone diameter from the treatment group, namely 0 mm, had a weak response to the growth of eschericia coli bacteria. The results of the antibacterial effectiveness test of ethanol extract of garlic on the growth of Staphylococcus aureus bacteria obtained the average clear zone diameter at concentrations of 5%, 10% and 15% from the treatment group, namely 0 mm, had a weak response to the growth of Staphylococcus aureus and eschericia coli bacteria. The conclusion of this study is that there is a significant difference in the effect of andaliman plant extract with a concentration of 15% on the growth of staphylococcus aureus, which is smaller than the effect of the antibiotic ciprofloxacin with an average diameter of the positive control clear zone of 26 mm. Keywords: Andaliman, Garlic, Staphylococcus Aureus